Regulations on the ownership of land and buildings in Indonesia - NURTI WIDAYATI; IAN NURPATRIA SURYAWAN; SRI VANDAYULI RIORINI (Jurnal Bisnis dan Akuntansi, 2017)
Before applicable Agrarian Law no. 5/1960, Indonesia apply two legal system in trouble land, namely based on Adat Law (Hukum Adat) and Civil Code (KUH Perdata). After applicable the Agrarian Law, Civil Code books part II still remain in force to the extent of land ownership as a motionless object (benda tak bergerak). Status of land ownership are divided into : property rights/Hak Milik (article 20 Agrarian Law), Hak Guna Usaha (article 28 Agrarian Law), Hak Guna Bangunan (article 35 Agrarian Law) and Hak Pakai (article 41 Agrarian Law). On article 19 Agrarian Law, explained that registration of land held by the Government of the Republic of Indonesia through the national land Agency and the task execution registration is done by the Head Office of the land in these areas, where the land registry implementation conducted by the head of Office assisted by land deed official (Pejabat Pembuat Akta Tanah/PPAT) and other officials who are assigned to perform a particular activity. According to article 21 paragraph (1) Agrarian Law, who can do the registration of property rights over land are citizens of Indonesia, as well as legal entities such as banks, government agencies and religious charities.